2021
DOI: 10.1186/s44149-021-00019-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and molecular characterizations of multidrug-resistant diarrheagenic E. coli of calf origin

Abstract: Escherichia coli has become one of the most important causes of calf diarrhea. The aim of this study is to determine the patterns of antimicrobial resistance of E. coli isolates from six cattle farms and to identify prominent resistance genes and virulence genes among the strains isolated from the diarrhea of calves. Antimicrobial susceptibility tests were performed using the disk diffusion method, and PCR was used to detect resistance and virulence genes. The prevalence of multidrug resistant (MDR) E. coli wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
1
2
1
Order By: Relevance
“…In the present study, S. Typhimurium was identified in cattle meat as the dominant serovar among other Salmonella spp. found in retail goat meat, consistent with findings from previous study [30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, S. Typhimurium was identified in cattle meat as the dominant serovar among other Salmonella spp. found in retail goat meat, consistent with findings from previous study [30].…”
Section: Discussionsupporting
confidence: 93%
“…Antimicrobial resistance in livestock production systems including common meatproducing animals such as cattle, goat, and chicken, particularly multidrug-resistant Salmonella enterica serovars Enteritidis and Typhimurium, remains largely unexplored in Bangladesh. Recent studies have highlighted the significant detection of MDR E. coli in commercial cattle, goats, and poultry [30][31][32]. Thus, the current study aimed to determine and compare the prevalence and antimicrobial resistance of ESBL-producing and MDR Salmonella enterica serovars Enteritidis and Typhimurium in retail meat samples in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Strains isolated from chickens showed an important ESBL production rate (9/22, 40.90%) that was lower than that found by Parvin et al (2020) (86%) [ 50 ] and higher than that observed in the study of Johar et al, 2021(3.8%) [ 45 ] in E. coli isolated from chickens. In cows with mastitis, 28% (7/25) of the E. coli isolates were phenotypically ESBL producers.…”
Section: Discussioncontrasting
confidence: 56%
“…This percentage is lower than that noted in a previous study which found 9 (7.26%) MDR E. coli isolates out of 150 isolates ( 28 ). Another study of faecal samples from cattle suffering diarrhoea found 21 (77.8%) and 28 (63.6%) MDR isolates of E. coli from samples of dairy cows and beef cattle, respectively ( 31 ). Escherichia coli isolates were tested in Ethiopia and 27 (100%) were MDR, 188 (100%) E. coli isolates in Nigeria were reported to be resistant to three to seven different classes of antibiotics, and 76 (53%) E. coli isolates demonstrated multidrug resistance in Vietnam ( 4 , 7 , 14 ).…”
Section: Discussionmentioning
confidence: 99%